Strengthening Independent Character Through P5 at State Senior High School - Jefri; Marzuki (Postgraduate, University of Mataram, 2025)
This study aims to analyze the impact of the implementation of the Pancasila Student Profile Strengthening Project (P5) on the development of independent character among students at SMA Negeri 1 Tanjung Palas Utara. Employing a qualitative case study design, data were collected through observation, interviews, and document analysis. Thematic analysis was used to interpret the data. The findings indicate that P5 enhances students’ independence, as shown by their increased initiative in completing tasks, improved time management, and willingness to take on leadership roles in school projects. Teachers observed that students became more proactive and less dependent on instructions. However, challenges emerged, such as students’ initial reluctance to act independently due to past teacher-centered habits and limited access to learning materials. Strategies to overcome these issues included structured mentoring, peer collaboration, and the integration of digital tools. The study concludes that P5 provides an effective framework for fostering self-reliance and resilience, contributing to the holistic development of students in alignment with Pancasila values.